2000
DOI: 10.1159/000016090
|View full text |Cite
|
Sign up to set email alerts
|

Recent Infection as a Risk Factor for Intracerebral and Subarachnoid Hemorrhages

Abstract: Previous infection has been shown to be a risk factor for acute cerebral ischemia. We tested the hypothesis that recent infection is also a risk factor for intracerebral hemorrhage (ICH) and subarachnoid hemorrhage (SAH). We performed a case-control study with 56 consecutive patients with ICH, 44 consecutive patients with SAH, and 56 and 44 neurological control patients, respectively. Infection within 4 weeks was associated with SAH independently of hypertension and smoking (p = 0.049). There was no significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 15 publications
1
30
0
2
Order By: Relevance
“…The evidence on recent infection in relation to the incidence of SAH is limited. 14,24,30,52,58 The results of a Canadian study from the Calgary region were comparable with our findings and showed a small but significant increase in the incidence of SAH during influenza epidemics, with a delay between increased influenza and SAH rates of 0.9 week. 14 A case-control study found that an upper respiratory tract infection was an independent trigger factor for SAH, but this study included only 44 patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The evidence on recent infection in relation to the incidence of SAH is limited. 14,24,30,52,58 The results of a Canadian study from the Calgary region were comparable with our findings and showed a small but significant increase in the incidence of SAH during influenza epidemics, with a delay between increased influenza and SAH rates of 0.9 week. 14 A case-control study found that an upper respiratory tract infection was an independent trigger factor for SAH, but this study included only 44 patients.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, this study's retrospective design, in which patients were asked if they had infections within 4 weeks prior to hospitalization, might have led to recall bias. 30 A case-crossover study on trigger factors for SAH found a relative risk of 2.4 (95% CI 0.3-16) for flu-like illness during the 24 hours prior to SAH. 58 Two other small case-control studies investigated antibody serum titers of influenza and other viral infections in patients with aneurysmal SAH.…”
Section: Discussionmentioning
confidence: 99%
“…Most longitudinal studies were initiated in the 1970s and were restricted to the US, Japanese, UK, Korean, and Finnish populations. Of the 23 case-control studies, 10 (63% of SAH cases) [12][13][14][15][16][17][18][19][20][21] were population based and 13 hospital based, [22][23][24][25][26][27][28][29][30][31][32][33][34] covering a variety of populations: American (United States), Latin American (Chile, Colombia, Mexico, Brazil, and Jamaica), European (Norway, Germany, Hungary, Portugal, Denmark, Yugoslavia, Slovenia, Finland, and the United Kingdom), African (Kenya, Zambia, and Zimbabwe), and Australasian (China, Indonesia, Thailand, Australia, New Zealand, and Japan). Overall, 3936 cases of SAH (892 cases in longitudinal studies [9 223 763 person-years of follow-up] and 3044 cases in case-control studies) were available for the analysis, thus allowing 1984 more cases of SAH to be analyzed than in the previous overview.…”
Section: Resultsmentioning
confidence: 99%
“…Our finding that most risk factors tend to be more hazardous in women than in men, although this difference is statistically nonsignificant, suggests that this may contribute to the higher incidence of SAH observed in women. Case-control 12,14,22,24,26,27 0.7 (0.5-0.8) †Totals represent pooled estimates for all available studies reporting data for both men and women separately or combined; there were a different No. of studies that contributed data to the overall effect estimates and No.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent systemic infection has been postulated as a trigger for subarachnoid hemorrhage in adults, perhaps related to the formation and rupture of aneurysms. 6 Association studies examining environmental risk factors for hemorrhage from vascular lesions in children are lacking. We hypothesized that antecedent recent infection or trauma may predispose children to incident hemorrhage from vascular lesions.…”
Section: Discussionmentioning
confidence: 99%